Revisiting global trends in TVET : reflections on theory and practice - (:unkn) unknown (UNEVOC, 2013)
The essays presented in this publication cover a wide range of current practices, ideas and debates in the field of technical and vocational education and training (TVET). The Third International Congress on TVET that took place in Shanghai in May 2012 played an important role in further enhancing the debate on the role of TVET in the 21st century, providing a forum for discussion on the challenges faced by the TVET systems and the appropriate responses to them. One of its important outcomes was the production of a set of key recommendations to governments and other TVET stakeholders in UNESCO Member States, presented under seven strands in the Shanghai Consensus. One of the aims of this publication is to provide some assistance in the implementation of these recommendations, through the fostering of reflection and sharing of knowledge, ideas and experience. The volume covers the following nine chapters: (1) Reconceptualizing TVET and development: a human capability and social justice approach; (2) Vocationalization of secondary and higher education: pathways to the world of work; (3) The attractiveness of TVET; (4) Learning through practice: beyond informal and towards a framework for learning through practice; (5) Work-based learning: Why? How?; (6) Why improved formal teaching and learning are important in technical and vocational education and training (TVET); (7) Career guidance and orientation; (8) TVET and entrepreneurship skills; (9) Technical and vocational education and training, and skills development for rural transformation. (Editor, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; L 2.1.1 Informelles Lernen; L 2.1.3 Erfahrungslernen; L 5 Beratung & Orientierung; I 2.1.3 Ländliche Region; Berufsbildungssystem; Attraktivität; Durchlässigkeit im Bildungssystem; Bildungschancengleichheit; Lernen und Arbeiten; Lernen am Arbeitsplatz; Berufsorientierung; Berufsberatung; Entrepreneurship Education; Ländlicher Raum